SDF-1/CXCR4 expression in head and neck cancer and outcome after postoperative radiochemotherapy. (August 2017) - De-Colle, Chiara; Mönnich, David; Welz, Stefan; Boeke, Simon; Sipos, Bence; Fend, Falko; Mauz, Paul-Stefan; Tinhofer, Inge; Budach, Volker; Jawad, Jehad Abu; Stuschke, Martin; Balermpas, Panagiotis; et al.
Highlights: Outcome after postoperative radiochemotherapy in head and neck cancer is unsatisfactory. We propose the chemokine axis SDF-1/CXCR4 as biomarker for patients stratification. SDF-1 overexpression is an negative prognostic marker for locoregional control. Prospective validation is warranted. Abstract: Introduction: Outcome after postoperative radiochemotherapy (RT-CT) for patients with advanced head and neck squamous cell carcinomas (HNSCC) remains unsatisfactory, especially among those with HPV negative tumours. Therefore, new biomarkers are needed to further define subgroups for individualised therapeutic approaches. Preclinical and first clinical observations showed that the chemokine receptor CXCR4 and its ligand SDF-1 (CXCL12) play an important role in tumour cell proliferation, survival, cancer progression, metastasis and treatment resistance. However, the data on the prognostic value of SDF-1/CXCR4 expression for HNSCC are conflicting. The aim of our hypothesis-generating study was to retrospectively explore the prognostic potential of SDF-1/CXCR4 in a well-defined cohort of HNSCC patients collected within the multicenter biomarker study of the German Cancer Consortium Radiation Oncology Group (DKTK-ROG). Material and methods: Patients with stage III and IVA HNSCC of the oral cavity, oropharynx and hypopharynx were treated with resection and adjuvant radiotherapy (RT) with ≥60 Gy and concurrent cisplatin-based chemotherapy (CT). Tissue micro-arrays (TMAs) from a total of 221 patients were generated from surgical specimens, 201 evaluated for the SDF-1 and CXCR4 expression by immunofluorescence and correlated with clinico-pathological and outcome data. Results: In univariate and multivariate analyses intracellular SDF-1 expression was associated with lower loco-regional control (LRC) in the entire patient group as well as in the HPV16 DNA negative subgroup. CXCR4 expression showed a trend for lower LRC in the univariate analysis which was not confirmed in the multivariate analysis. Neither for SDF-1 nor CXCR4 expression associations with distant metastasis free or overall survival were found. Conclusions: Our exploratory data support the hypothesis that overexpression of intracellular SDF-1 is an independent negative prognostic biomarker for LRC after postoperative RT-CT in high-risk HNSCC. Prospective validation is warranted and further exploration of SDF-1/CXCR4 as a potential therapeutic target to overcome treatment resistance in HNSCC appears promising.